Development and Validation of the Safe Parenteral Medication Administration Self-Efficacy Scale - OKUROĞLU, GÜLTEN; ŞAHİN ORAK, NURAY; ALPAR, ŞULE (SLACK INC, 2021)
Background: This study aimed to develop a valid and reliable measurement instrument for determining the self-efficacy perceptions of nurses concerning safe medication practices. Method: The study was conducted at the hospital of a state university in Istanbul, Turkey, between August and December 2016. The sample consisted of 278 nurses. Results: The exploratory factor analysis indicated the scale had a single-factor structure that explained 47.92% of the total variance. The remaining 76 items had factor loads ranging from .50 to .87. The item-total correlations varied between .49 and .86, and Cronbach's alpha coefficient for the scale was .98. Conclusion: The results of the analysis show the items constituting the scale have validity and reliability criteria that can measure the self-efficacy of nurses related to parenteral medication administration.
Keywords: ERRORS; NURSES; PREVENTION; ATTITUDES; VALIDITY; QUALITY